1985
DOI: 10.1111/j.1752-1688.1985.tb05369.x
|View full text |Cite
|
Sign up to set email alerts
|

FLOODPLAIN STORAGE AND LAND USE ANALYSIS AT THE WOODLANDS, TEXAS1

Abstract: The Woodlands, a totally planned community north of Houston, Texas, was studied in detail in an effort to develop a master drainage plan which minimizes adverse impact on the 100‐year floodplain. A total of 40 HEC‐1 and HEC‐2 computer runs were made to evaluate various development, channelization, and reservoir storage options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Another finding that corresponds to previous studies is that the pattern of development in the watershed has an influence on peak discharge (Bedient et al, 1985). In the Panther Creek watershed, there are more A and B soils than C and D soils in the lower reaches.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Another finding that corresponds to previous studies is that the pattern of development in the watershed has an influence on peak discharge (Bedient et al, 1985). In the Panther Creek watershed, there are more A and B soils than C and D soils in the lower reaches.…”
Section: Discussionsupporting
confidence: 74%
“…The Panther Creek watershed boundary was delineated using the outlet located at the confluence of Panther Creek and Spring Creek (Bedient et al, 1985). The drainage area of the watershed is 94.2 km 2 .…”
Section: Study Sitementioning
confidence: 99%
“…Other quantitative and modelling assessments have been made regarding The Woodlands landscape performance. Bedient, Flores, Johnson, and Pappas (1985) compared more than a dozen development scenarios and concluded that The Woodlands development plan mitigates flooding, and Doubleday, Sebastian, Luttenschlager, and Bedient (2013) further showed that The Woodlands can attenuate peak discharges during 100-year storm events. Compared with adjacent Houston communities, The Woodlands showed substantially lower levels of forest fragmentation (Kim & Ellis, 2009), lower run-off volume and pollutant loadings , and on average, 2°C lower land surface temperature (Sung, 2013;.…”
Section: Introductionmentioning
confidence: 97%
“…Development started around the same period in these two watersheds in the 1970s, whereas stormwater management methods differ. The Woodlands has been well-managed as a planned community from its inception [45,47]. Ecological planner Ian McHarg laid out a suite of decentralized, infiltration-based drainage designs to reduce runoff volume and improve water quality [48][49][50][51].…”
Section: Study Sitementioning
confidence: 99%
“…One of the projects, The Woodlands, is a renowned large-scale community development. It is a precursor of the USEPA's GI design initiative: a series of integrated GI design strategies were used to meet flood control and stormwater quality goals [44][45][46][47]. Several recent studies have demonstrated the effectiveness of The Woodlands GI design on flood mitigation [31,32,46].…”
Section: Introductionmentioning
confidence: 99%